2015
DOI: 10.2147/ijn.s77372
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic thermoablation stimuli alter BCL2 and FGF-R1 but not HSP70 expression profiles in BT474 breast tumors

Abstract: Magnetically induced heating of magnetic nanoparticles (MNP) in an alternating magnetic field (AMF) is a promising minimal invasive tool for localized tumor treatment that eradicates tumor cells by applying thermal stress. While temperatures between 42°C and 45°C induce apoptosis and sensitize the cells for chemo- and radiation therapies when applied for at least 30 minutes, temperatures above 50°C, so-called thermoablative temperatures, rapidly induce irreversible cell damage resulting in necrosis. Since only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Although this finding was in accordance with an earlier publication analyzing the HSP70 expression at 2 h after the short-term application of magnetic heating, this study demonstrated the persistence of HSP70 levels up to 48 h. 17 Due to its chaperon function, HSP70 was reported to be upregulated upon cellular stress as caused by heat or toxic stimuli. 68,69 Therefore, the instant elevation of HSP70 in the MTX/MNP group and the time-dependent upregulation in the MNP group were hypothesized to be based on the application of MTX/MNPs or MNPs which probably were recognized as toxic stimuli.…”
Section: Impairment Of Cellular Survival Signalingsupporting
confidence: 92%
See 1 more Smart Citation
“…Although this finding was in accordance with an earlier publication analyzing the HSP70 expression at 2 h after the short-term application of magnetic heating, this study demonstrated the persistence of HSP70 levels up to 48 h. 17 Due to its chaperon function, HSP70 was reported to be upregulated upon cellular stress as caused by heat or toxic stimuli. 68,69 Therefore, the instant elevation of HSP70 in the MTX/MNP group and the time-dependent upregulation in the MNP group were hypothesized to be based on the application of MTX/MNPs or MNPs which probably were recognized as toxic stimuli.…”
Section: Impairment Of Cellular Survival Signalingsupporting
confidence: 92%
“…15,16 These high temperatures cause necrosis even after a relatively short time of thermal exposure, by inducing irreversible cellular damage, such as the inhibition of DNA repair, and protein denaturation. 17 To further amplify the effect of magnetic heating alone, a combinatory treatment of the target tissue by an additional coupling of drugs (eg, chemotherapeutics) to the MNPs is possible. 18 In this regard, the chemotherapeutic drug methotrexate (MTX), an antifolate which interferes with the cellular nucleotide metabolism and DNA synthesis, was shown to be coupled stably to MNPs (MTX/MNPs) and exhibited a comparable toxicity to free MTX.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Moreover, MNP can be heated in an alternating magnetic field, allowing a localized sensitization or destruction of tumor cells or tumor tissue by hyperthermal or even thermoablative temperatures. [8][9][10][11] For magnetic heating purposes, iron oxide MNP with a clustered magnetite or maghemite core and an appropriate coating (polyethylene glycol [PEG], dextran, dimercaptosuccinic acid [DMSA], etc) have been shown to exhibit good heating capabilities and biocompatibility. 10,[12][13][14][15][16] One chemotherapeutic drug that can effectively be coupled to MNP is methotrexate (MTX).…”
Section: Introductionmentioning
confidence: 99%
“…In our recent study, immunohistochemical analysis of tumor tissue slices revealed a distinct downregulation of BCL2 and FGF-R1 on the protein level, whereas the HSP70 level remained unchanged. At the same time, tumor tissue exhibited large apoptotic and necrotic areas in regions with high MNP concentration [33]. Importantly, multidrug resistance-associated proteins (MRPs) are known to be responsible for many therapeutic failures in current oncological treatments.…”
Section: Impact Of Magnetic Heating Of Cells and Tissuesmentioning
confidence: 99%